2022
DOI: 10.1681/asn.2022020139
|View full text |Cite
|
Sign up to set email alerts
|

Blocking CCL8-CCR8–Mediated Early Allograft Inflammation Improves Kidney Transplant Function

Abstract: BackgroundIn kidney transplantation, early allograft inflammation impairs long-term allograft function. However, precise mediators of early kidney allograft inflammation are unclear, making it challenging to design therapeutic interventions.MethodsWe used an allogeneic murine kidney transplant model in which CD45.2 BALB/c kidneys were transplanted to CD45.1 C57BL/6 recipients.ResultsDonor kidney resident macrophages within the allograft expanded rapidly in the first 3 days. During this period, they were also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…In the presence of AXL inhibition by bemcentinib, the resulting Mϕs are not only diminished in number ( Figure 1C ) but also in their ability to present alloantigen ( Figure 1D ), with a subsequent reduction in the activation and proliferation of allospecific T cells ( Figure 2B ). Our monocle psuedotime analysis of a single-cell RNA-Seq data set of murine heart allografts, we observed a similar upregulation of the Axl transcripts during early intragraft MC-to-Mϕ differentiation ( Figure 3E ), concordant with our published findings in a murine allogeneic kidney transplant model ( 1 ). Lastly, transient AXL blockade using bemcentinib treatment in a murine heart transplant model leads to a global reduction in intragraft inflammation and to an extended allograft survival ( Figures 4 – 6 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In the presence of AXL inhibition by bemcentinib, the resulting Mϕs are not only diminished in number ( Figure 1C ) but also in their ability to present alloantigen ( Figure 1D ), with a subsequent reduction in the activation and proliferation of allospecific T cells ( Figure 2B ). Our monocle psuedotime analysis of a single-cell RNA-Seq data set of murine heart allografts, we observed a similar upregulation of the Axl transcripts during early intragraft MC-to-Mϕ differentiation ( Figure 3E ), concordant with our published findings in a murine allogeneic kidney transplant model ( 1 ). Lastly, transient AXL blockade using bemcentinib treatment in a murine heart transplant model leads to a global reduction in intragraft inflammation and to an extended allograft survival ( Figures 4 – 6 ).…”
Section: Discussionsupporting
confidence: 90%
“…We have previously demonstrated in a murine allogeneic kidney transplant model that recipient MCs first arrive at the transplanted kidney as Ly6C + F4/80 – cells in a donor Mϕ-dependent, CCL8/CCR8 axis–dependent manner ( 1 , 2 ). In this model, pseudotime analysis using single-cell transcriptomics of the kidney allograft revealed that graft-infiltrating recipient MCs quickly differentiated to inflammatory Mϕs (iMϕs), and this process appeared to correlate with a transient upregulation of the receptor tyrosine kinase AXL in these cells ( 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Equipped with the ability to interrogate the transcriptome and clonality of graft-infiltrating cells at a single-cell level, we showed in an allogeneic murine kidney transplant model that graft-infiltrating αβ and γδ T cells both express surface CCR8 and that blocking the CCL8-CCR8 axis severely impairs the recruitment of these cells to the kidney allograft. 89 Our data provide evidence that the CCL8-CCR8 axis is a vital linchpin between donor kidney resident macrophages and early immune cell infiltration and therefore represents a promising therapeutic target.…”
Section: Clinical Studies With Scrna-seqmentioning
confidence: 67%